1996
DOI: 10.1016/0300-2977(95)00059-3
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of deep vein thrombosis, an overview

Abstract: A bstractBecause clinical signs and symptoms are unreliable the diagnosis of deep vein thrombosis (DVT) should be objectified. Advantages and disadvantages of contrast venography, plethysmography, ultrasound techniques, fibrino gen leg scanning, computer-assisted tomography, magnetic resonance imaging and blood tests are discussed. In patients with a first event of suspected DVT non-invasive methods like serial plethysmography or ultrasound testing are sensitive and specific enough to make a treatment decision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

1999
1999
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 120 publications
0
11
0
2
Order By: Relevance
“…With the aid of non‐invasive investigations such as VDUS the diagnosis can be made with more certainty and with no patient morbidity. Multiple studies have shown that VDUS has a high sensitivity and specificity in diagnosing both axial and calf DVT 1−9 . A downside is that VDUS is being increasingly ordered to rule out DVT in patients whose pretest probability of DVT is low.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the aid of non‐invasive investigations such as VDUS the diagnosis can be made with more certainty and with no patient morbidity. Multiple studies have shown that VDUS has a high sensitivity and specificity in diagnosing both axial and calf DVT 1−9 . A downside is that VDUS is being increasingly ordered to rule out DVT in patients whose pretest probability of DVT is low.…”
Section: Discussionmentioning
confidence: 99%
“…Venous duplex ultrasound scanning (VDUS) is generally recognized as the initial diagnostic test of choice for suspected deep venous thrombosis (DVT), with a high sensitivity and specificity in detecting both axial and calf vein thrombi 1−9 . It was a protocol recommendation of the Intersocietal Commission for the Accreditation of Vascular Laboratories (ICAVL) that both legs be scanned even for unilateral symptoms of DVT 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Es sprechen drei Gru Ènde gegen den Einsatz des 125-Iod-Fibrinogen-Testes als Screeningverfahren: Die Belastung des Patienten mit radioaktiven Substanzen, das nicht vo Èllig auszuschlieûende Infektionsrisiko und die mangelnde Korrelation mit klinisch signifikanten Thrombosen [17]. Florda et al stellten 1995 bei 2 578 Patienten fest, daû sich nur bei 14 % der positiven nuklearmedizinischen Ergebnisse tatsa Èchlich phlebographisch eine Thrombose besta Ètigte [13].…”
Section: Farbcodierte Duplexsonographie Als Untersuchungsmethodeunclassified
“…Die Phlebographie gilt zur Zeit nach wie vor als der Goldstandard zur Diagnose veno Èser Thrombosen. Neben der unvermeidlichen Strahlenbelastung stellten Kontrastmittelunvertra Èglichkeiten bislang das Hauptrisiko der Untersuchung dar, welches jedoch durch den Einsatz niederosmolarer Kontrastmittel deutlich verringert wurde [17,29,30]. Dennoch ist diese Untersuchung fu Èr ein reines Screeningverfahren aufgrund des Restrisikos und der subjektiven Belastung fu Èr den Patienten letztendlich schwer vertretbar.…”
Section: Farbcodierte Duplexsonographie Als Untersuchungsmethodeunclassified
“…Whereas a constant filling defect is usually considered to represent acute venous thrombosis, the other findings may also result from old thrombi or artifacts. Janssen et al(10) interviewed 50 patients about side effects. Of these, 20% experienced unpleasant side effects.…”
mentioning
confidence: 99%